HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN DI PUSKESMAS JAYA MUKTI - Dachi, Ester Priska; ", Bayhakki "; Hasneli, Yesi " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractHealth service and quality of patient satisfaction influence each other. A good health care will produce good quality and will make high level of patient satisfaction of the health service itself. This study aimed to determine the relationship of health care quality and patient satisfaction in Jaya Mukti Public Health Center Dumai City. The study design used was correlation with cross sectional approach. The samples were 100 respondents recruited using simple random sampling. Measuring instruments used were the patient satisfaction questionnaires and quality health services. The analysis using univariate analysis to determine the frequency distribution and bivariate using chi-square test. The results showed good quality of health care as many as 67 respondents (67%), and satisfied with the health services as much as 52 respondents (52%). The statistical result obtained Ï-value (0.000) <Î± (0.05), so there was relationship between the quality of healthcare and patient satisfaction in Jaya Mukti Public Health Center Dumai City. The results of this study recommends for health workers, especially nurses to improve the quality of services to achieve patient satisfaction with health services provided.